Reading the right text : an anthology of contemporary Chinese drama - Chen, Xiaomei, 1954- (University of Hawai'i Press, 2003)
Reading the Right Text introduces six new plays from contemporary China, five of which are translated here into English for the first time. Chosen from a wide variety of well-received dramas of the period, each play represents the traditions and changes in a particular subgenre: regional theater, proletarian theater, women's theater, history plays, and experimental theater. Xiaomei Chen's wide-ranging and perceptive introduction locates the plays in the political and cultural history of modern China to demonstrate the interrelationship between theater, history, society, and everyday experience. She highlights the origin and development of the different sub-genres and outlines critical approaches from numerous fields, including gender studies, performance studies, subaltern studies, and comparative cultural studies. Quite apart from their importance as theater, these plays are crucial for a fully rounded understanding of the cultural dynamics involved in the transition from Maoist to post-Mao China, from socialist realist drama to the post-socialist response to a market economy and a society in flux.